Republic of Belarus : Technical Assistance Report-Report on External Sectoral Accounts Mission (November 11-22, 2019). - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2020)
The contents of this report constitute technical advice provided by the staff of the IMF to the authorities of the Republic of Belarus in response to their request for technical assistance. The principal purposes of the mission were to review with the National Statistical Committee of the Republic of Belarus (Belstat) current data sources; identify data sources that needed to be improved; demonstrate how to construct the tables; and prepare a work plan. The mission noted a few instances where the data could be improved through the provision of more detail or verification that the classification had been done correctly. The mission worked with Belstat staff to show how the currently available data sources should be used to compile sector balance sheets and how to use these data to construct the sector financial accounts. The mission recommended that Belstat prepare the financial balance sheets (FABS) for 2017 using the data presently available. The mission recommended that Belstat staff be encouraged to apply for courses on the FABS, such as those offered by the IMF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet